Efficacy of a whole-body vibration intervention to effect exercise tolerance and functional performance of the lower limbs of people with chronic obstructive pulmonary disease - Furness Trentham; Bate Nicole; Welsh Liam; Naughton Geraldine; Lorenzen Christian (BMC Pulmonary Medicine, 2012)
Abstract Background Chronic obstructive pulmonary disease (COPD) is a respiratory condition characterised by dyspnoea, excessive sputum production, chronic cough, bronchitis and emphysema. Functionally, exercise tolerance is poor for people with COPD and is linked to difficulty in performing daily tasks. More specifically, exercise difficulties are due partly to dyspnoea and lower limb skeletal muscle dysfunction. The benefit of exercise that does not exacerbate the disease while improving exercise tolerance is salient. Whole-body vibration (WBV) is a mode of physical activity known to improve muscular function of the lower limbs, yet efficacy has not been investigated for a WBV intervention conducted in a home-based setting for people with COPD. Methods/design This clinically registered trial is a non-randomised placebo cross-over intervention based in the home of each participant (ACTRN12612000508875). Participants diagnosed with COPD will complete a six-week WBV intervention and then after a two-week washout period, will complete a six-week placebo training intervention. Participants will complete sessions twice a week. The duration of the trial is 14 weeks. Community-dwelling older adults with COPD will provide informed voluntary consent to participate. Outcome measures will include immediate, acute, and long-term responses to exercise. Discussion Quantifying responses to WBV among people with COPD will allow discussion of efficacy of WBV as a mode of physical activity. The skill required by the participant to perform physical activity with WBV is not demanding and may enhance habitual sustainability. The results of this trial could be used to support further research in both clinical and community settings. Trial registration Australian New Zealand Clinical Trials Registry (ANZCTR12612000508875)